2021
DOI: 10.1101/2021.07.08.451678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical genetic program forDrosophilaimaginal disc regeneration revealed by single-cell analysis

Abstract: Whether regeneration is primarily accomplished by re-activating gene regulatory networks used previously during development or by activating novel regeneration-specific transcriptional programs remains a longstanding question. Currently, most genes implicated in regeneration also function during development. Using single-cell transcriptomics in regenerating Drosophila wing discs, we identified two regeneration-specific cell populations within the blastema. They are each composed of cells that upregulate multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(95 reference statements)
1
1
0
Order By: Relevance
“…We further observe an up-regulation of markers of tissue patterning and proliferation in cluster 𝝰 relative to cluster 𝝱, like wingless (wg), Wnt oncogeneanalog 6 (Wnt6) (Figure 1.c, p-adj𝝰/𝝱<10e -3 , log2FC𝝰/𝝱>1) and CyclinE (CycE) (Figure 3.d, log2FC𝝰/𝝱>0.8). In this line, we also find evidence for an up-regulation of the pro-regenerative marker Ets at 21C (Ets21C) (Worley et al, 2021), with a combined enrichment of its gene expression (p-adj<10e -3 , log2FC>8) and its binding motif in cluster 𝝰 (cistarget, NES=3.35). Consistent with the higher enhancer activity of the Stat92E eGRN in wound 𝝰 compared to 𝝱 (Figure 3.a-b), we find a significant overlap between the 𝝰 marker genes and a study that identified JAK/STAT as coordinating cell proliferation during wing disc regeneration (GSEA, NES=1.292) (Katsuyama et al, 2015).…”
Section: Multi-ome Gene Regulatory Network Reconstructionsupporting
confidence: 69%
“…We further observe an up-regulation of markers of tissue patterning and proliferation in cluster 𝝰 relative to cluster 𝝱, like wingless (wg), Wnt oncogeneanalog 6 (Wnt6) (Figure 1.c, p-adj𝝰/𝝱<10e -3 , log2FC𝝰/𝝱>1) and CyclinE (CycE) (Figure 3.d, log2FC𝝰/𝝱>0.8). In this line, we also find evidence for an up-regulation of the pro-regenerative marker Ets at 21C (Ets21C) (Worley et al, 2021), with a combined enrichment of its gene expression (p-adj<10e -3 , log2FC>8) and its binding motif in cluster 𝝰 (cistarget, NES=3.35). Consistent with the higher enhancer activity of the Stat92E eGRN in wound 𝝰 compared to 𝝱 (Figure 3.a-b), we find a significant overlap between the 𝝰 marker genes and a study that identified JAK/STAT as coordinating cell proliferation during wing disc regeneration (GSEA, NES=1.292) (Katsuyama et al, 2015).…”
Section: Multi-ome Gene Regulatory Network Reconstructionsupporting
confidence: 69%
“…The integrated dataset overlayed T1, T2, and T3 individual samples and identified four distinct clusters ( Figure 1 D). The largest cluster represented the leg disc epithelium, which expressed epithelial markers Fasciclin 3 ( Fas3 ) and narrow ( nw ) ( Figure 1 E) [ 21 ]. Expression of Sp1 and Ultrabithorax ( Ubx ) confirmed that the cells originated from L3 discs [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%